Stress-induced cognitive dysfunction: hormone-neurotransmitter interactions in the prefrontal cortex - Shansky, Rebecca M.; Lipps, Jennifer (Frontiers in Human Neuroscience, 2013)
The mechanisms and neural circuits that drive emotion and cognition are inextricably linked. Activation of the hypothalamic-pituitary-adrenal (HPA) axis as a result of stress or other causes of arousal initiates a flood of hormone and neurotransmitter release throughout the brain, affecting the way we think, decide, and behave. This review will focus on factors that influence the function of the prefrontal cortex (PFC), a brain region that governs higher-level cognitive processes and executive function. The PFC becomes markedly impaired by stress, producing measurable deficits in working memory. These deficits arise from the interaction of multiple neuromodulators, including glucocorticoids, catecholamines, and gonadal hormones; here we will discuss the non- human primate and rodent literature that has furthered our understanding of the circuitry, receptors, and signaling cascades responsible for stress-induced prefrontal dysfunction.